(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2020)
Written interview in May 2020 with Andreas Schleicher, director of education at the OECD – Organization for Economic Cooperation and Development, focusing on educational issues that directly or indirectly concern theatre education. The interview was also addressed to Stéphan Vincent-Lancrin, Ellen Winner and Thalia Goldstein, authors of an OECD book dedicated to teaching arts in schools. The approached topics comprehended the importance of artistic education, connections of artistic education with competencies, public policies in education and the global economic agenda. The interview is preceded by a preamble authored by the interviewer.